Three new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China - Su, Jing-Jing; Li, Xiao-Yan; Zhou, Hong-Zhang (Zootaxa, 2020)
This paper reports three new species of the genus Nazeris Fauvel, 1873 from mainland China, namely Nazeris mahuanggouensis Su, Li and Zhou, sp. nov. and Nazeris zhouhaishengi Su, Li and Zhou, sp. nov. from Sichuan Province, Nazeris wuluozhenensis Su, Li and Zhou, sp. nov. from Guizhou Province. For all species included we offer color plates of normal light photos for general morphology and detailed aedeagus structures.